2019
DOI: 10.4103/jfmpc.jfmpc_652_19
|View full text |Cite
|
Sign up to set email alerts
|

Radiological difference between new sputum-positive and sputum-negative pulmonary tuberculosis

Abstract: Introduction:The current guidelines for the diagnosis of pulmonary tuberculosis (PTB) are based primarily on the demonstration of acid-fast bacilli (AFB) on sputum microscopy and chest radiograph. Knowing various radiological manifestations and their association with sputum microscopy findings can allow for early diagnosis and early initiation of treatment.Aims:This study was performed to compare the chest radiograph features seen in sputum-positive and sputum-negative tuberculosis patients, respectively.Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…We also analysed the radiological pro ile among the 36 cases detected on Gene Xpert and found that 44%had non homogenous opacity, 25 % had homogenous opacity with air bronchogram, 17% had cavitation, 8% had nodules and 6 % had hilar enlargement. In a study done by Deependra k rai et al patchy in iltrates and cavitation was observed in sputum positive compared to sputum negative cases, but in our study we could not make that comparison as we have studied only sputum negative PTB suspects (Rai et al, 2019).…”
Section: Resultsmentioning
confidence: 71%
“…We also analysed the radiological pro ile among the 36 cases detected on Gene Xpert and found that 44%had non homogenous opacity, 25 % had homogenous opacity with air bronchogram, 17% had cavitation, 8% had nodules and 6 % had hilar enlargement. In a study done by Deependra k rai et al patchy in iltrates and cavitation was observed in sputum positive compared to sputum negative cases, but in our study we could not make that comparison as we have studied only sputum negative PTB suspects (Rai et al, 2019).…”
Section: Resultsmentioning
confidence: 71%
“…12 In another Indian study frequency of patchy consolidation (78.9% vs 49.5%) and cavitation (36.8% vs 15.6%) was significantly higher in smear positive patients. 2 CXR features of smear negative pulmonary TB cases differs from smear positive pulmonary TB cases probably due to lower bacillary load. Parenchymal lobe involved showed upper and middle lobes to be more commonly involved.…”
Section: Discussionmentioning
confidence: 87%
“…1 Prompt diagnosis of TB facilitates timely therapeutic interventions and minimizes community transmission. 2 For the diagnosis of pulmonary TB, smear microscopy and culture of the respiratory specimen are considered as the gold standard. Culture has the disadvantage of long turn-around time, which limits its usefulness as an initial diagnostic test.…”
Section: Introductionmentioning
confidence: 99%
“…Research in the application of deep learning to radiology (10,11) is a rapidly growing field as a result of its promising performance in disease detection, such as pleural effusion and cardiomegaly detection on chest radiographs (12,13), and mediastinal lymph node and lung nodule detection on computed tomography (CT) (14,15). Researchers have realized that AI-based chest X-ray (CXR) is a very promising tool for diagnosing TB, especially in resource-limited rural areas (10).…”
Section: Introductionmentioning
confidence: 99%